The infection of ideas and the measures of restraint: the case of the 1841 inventory of the Convento dei Frati Cappuccini in Lugano (Altre Modernità, 2023)
The provincial archives of the Swiss Capuchins in Lucerne preserve the 1841 inventory, originally compiled by Cherubino da Ligornetto, guardian of the Capuchin convent in Lugano, with interventions by Mr. Giacomo Beretta and Mr. Pasquale Lurati, in compliance with the Law of the 19th of June 1803 and its subsequent resolutions. The document includes information concerning the shelves of banned books in the Library of the Capuchin Convent, Lugano, known today as the Biblioteca Salita dei Frati. Unlike the expurgated editions, which were shown during the guided tour of the Library on the 29th of September 2022, these do not show deletions of text, but rather display some handwritten annotations, such as the note "forbidden" placed on the front flyleaves. This shows that, over the centuries, book censorship could take many a form.
Keywords: Salita dei Frati Library, collections, banned books, archival collections